2019
DOI: 10.5114/aoms.2018.73128
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus lactone inhibits in vitro gastrinoma cancer cell growth through apoptosis induction, sub-G1 cell cycle arrest, DNA damage and loss of mitochondrial membrane potential

Abstract: A b s t r a c t Introduction:The purpose of the present study was to evaluate the antiproliferative activity of dehydrocostus lactone against human BON-1 cancer cell lines and to explore the possible underlying mechanism. Material and methods: MTT cell viability assay was used to determine cytotoxic effects of dehydrocostus lactone in BON-1 cells. Fluorescence and transmission electron microscopic (TEM) techniques were used to study the effect of the compound on cellular morphology and apoptosis. Flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Increased concentrations of the CPEE impact cell death, as evidenced by an increase in the percentage of sub-G1 (M1) cells and an increase in cell cycle arrest G0-G1 phase. This finding is consistent with previous research indicating that increasing the concentration of extracts of a cell-induced product increases cell death by increasing sub-G1 (M) and G0-G1 cell cycle arrest [56,57]. The CPEE could inhibit the cell cycle, causing cell accumulation in a hyperdiploid, and then undergo apoptosis.…”
Section: Evaluation Of Cell Cycle Arrestsupporting
confidence: 93%
“…Increased concentrations of the CPEE impact cell death, as evidenced by an increase in the percentage of sub-G1 (M1) cells and an increase in cell cycle arrest G0-G1 phase. This finding is consistent with previous research indicating that increasing the concentration of extracts of a cell-induced product increases cell death by increasing sub-G1 (M) and G0-G1 cell cycle arrest [56,57]. The CPEE could inhibit the cell cycle, causing cell accumulation in a hyperdiploid, and then undergo apoptosis.…”
Section: Evaluation Of Cell Cycle Arrestsupporting
confidence: 93%
“…Fluorescent dye rhodamine 123 can directly distribute in the mitochondrial matrix according to the intensity of the MMP, and its fluorescence intensity can reflect the change of the MMP . Therefore, rhodamine 123 could be used as an indicator to detect the effect of compound SCU2028 on the MMP of R.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent dye rhodamine 123 can directly distribute in the mitochondrial matrix according to the intensity of the MMP, and its fluorescence intensity can reflect the change of the MMP. 23 Therefore, rhodamine 123 could be used as an indicator to detect the effect of compound SCU2028 on the MMP of R. solani. As shown in Figure 3, the result showed that the fluorescence intensity of the mycelium mitochondria in the control group was strong, which indicated that the mitochondrial membrane was complete (Figure 3A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Research has associated the anticancer activities of dehydrocostus lactone to the inhibition of cancer cell proliferation and induction of cancer cell apoptosis [ 37 ], inhibition of migration and invasion and inhibition of angiogenesis [ 38 ]. The induction of apoptosis is associated with increased protein [ 37 ], a reduction in mitochondrial membrane potential [ 39 ] and the release of cytochrome C, triggering the intrinsic pathway of apoptosis and/or the activation of caspases [ 40 , 41 , 42 ]. Another, caryophyllene oxide, possesses strong anticancer properties [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%